Poising of the arginine pool and control of bioluminescence in Beneckea harveyi. - Makemson, J C (1979)
Arginine dramatically stimulates bioluminescence in the marine bacterium Beneckea harveyi growing in minimal media, an effect that is due to increases in both the synthesis and expression of luciferase. To elucidate the mechanism of this phenomenon, studies were made of the transport and metabolism of arginine in B. harveyi. The transport of arginine and lysine involves two kinetically distinct transport systems for the uptake of arginine and lysine. In contrast, ornithine is transported only by a system common to all three amino acids. The internal amino acid pools were measured in mutants that do not show stimulation of bioluminescence by arginine and in wild-type cells that do. In minimal media, the internal arginine pools are undetectably low. Furthermore, exogenously added labeled arginine is rapidly transported and converted to citrulline and argininosuccinate. The results can be accommodated by a model in which the internal arginine is poised at a very low concentration; the stimulatory effect of exogenous arginine on luciferase biosynthesis occurs at the transcriptional level, and the actual mediator can be either arginine or argininyl transfer ribonucleic acid.